PENERAPAN PENDEKATAN RULE OF REASON OLEH KPPU DALAM DUGAAN PENGENAAN HARGA EKSESIF (STUDI KASUS PUTUSAN KPPU NOMOR PERKARA 03/KPPU-I/2017) - Sanjaya, Indra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
To assess whether a particular action of a business actor violates the provisions in Statute Number 5 of 1999, the KPPU and the Court may apply the per se illegal approach or rule of reason, depending on the formulation of the provisions allegedly violated. The rule of reason approach is an approach used by business competition authorities to make an evaluation of the consequences of certain agreements or business activities, to determine whether an agreement or activity is inhibiting or supporting competition. This paper analyzes the rule of reason approach applied by KPPU in cases with Case Number 03 / KPPU-I / 2017 to determine whether PT. Angkasa Pura II (Persero) which does not reduce the cost of shipping and taking cargo at Kualanamu Airport, even though its workload has been reduced, can be classified as a form of monopolization and constitutes a violation of the provisions of Article 17 paragraph (1) and paragraph (2) of Statute Number 5 of 1999. The results of the study showed that the application of the rule of reason by KPPU was carried out through 4 (four) steps, namely: (1). Market identification; (2) Identification of market power; (3) Identification of abuse of dominant position; (4) Identification of impacts on the public interest. Through the application of the rule of reason, KPPU decides that the actions of PT. Angkasa Pura II is a form of monopolization and that the action fulfills the elements in Article 17 paragraph (1) and (2) of Statute Number 5 of 1999.